Multilevel Operation in Scaled Back-End-of-Line Ferroelectric FETs With a Metal Interlayer - Chiara Rossi; Daniel Lizzit; David Esseni (IEEE Access)
Multi-level operation, conventionally obtained in ferroelectric devices thanks to a domain-dependent inhomogeneous polarization, poses a big challenge for highly-scaled ferroelectric devices, where the number of ferroelectric domains is drastically reduced. In this work, we study a highly scaled back-end-of-line (BEOL) compatible, ferroelectric field-effect transistor (FeFET) that integrates a metal interlayer in the gate stack. Through analytical models and calibrated TCAD simulations, we show how this device can achieve a multi-level operation exploiting the interplay between the ferroelectric polarization and the charge in the metal interlayer. Such a working principle does not rely on a domain-dependent inhomogeneous polarization, and the device operation is thus ensured also for a homogeneous ferroelectric material. We also demonstrate that the charge in the interlayer can effectively stabilize the ferroelectric polarization even in the absence of a high concentration of trapped charges in the gate stack. The potentiation and depression curves for the readout conductance confirm that the proposed device can be operated as a memristor for neuromorphic computing applications. Moreover, we show how the choice of the dielectric in the metal-ferroelectric-dielectric-metal gate stack can be used as a design knob to reduce the device operation voltage.